2020
DOI: 10.1002/ese3.696
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the nonlinear gas flow and stress‐dependent permeability of shale fractures

Abstract: The fluid flow characteristics in shale fractures are of great significance for shale gas reservoir evaluation and exploitation. In this study, artificial tension fractures in shale were used to simulate the hydraulic fractures formed by fracturing, and a gas flow test under different pressure gradients was conducted. The nonlinear gas flow and stress‐dependent permeability characteristics were analyzed. The experimental results show the following: (a) CO2 flow in shale fractures exhibits strong nonlinearity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…When the influence of fracture structure is considered, the effective stress can be taken as the macroscopic average for the fractured rock mass, and the effective stress coefficient α can be regarded as 1 for simplicity. The gas flow pressure in the fracture can be regarded as the average of the inlet pressure and outlet pressure [22],…”
Section: Test Schemementioning
confidence: 99%
See 1 more Smart Citation
“…When the influence of fracture structure is considered, the effective stress can be taken as the macroscopic average for the fractured rock mass, and the effective stress coefficient α can be regarded as 1 for simplicity. The gas flow pressure in the fracture can be regarded as the average of the inlet pressure and outlet pressure [22],…”
Section: Test Schemementioning
confidence: 99%
“…The existing literature is mostly focused on nonlinear fluid seepage through fractured rock masses in sandstone, shale, and marble, whereas seepage in rough fractures in coal is rarely studied in terms of the influence of fracture structure, environmental factors, and fluid properties. In addition, field tests, laboratory tests, and simulations have found that the nonlinear aspects of flows can be described by the Forchheimer equation [18] and Izbash equation [19], but the scope of application of both has not been clarified [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The seepage characteristic curves of shale with different fracture widths are shown in Figure 4(b). Similarly, the smaller the fracture width, the more the seepage curve deviates from the origin, and the more obvious its nonlinear permeability characteristics [29]. The main reason is that the fracture width alters the seepage volume of shale rock, while the seepage trajectory is the extended by fracture length.…”
Section: Effect Of Internal Microfracture Width On Seepagementioning
confidence: 99%
“…The result indicated that the smaller the effective stress (Boit) coefficient obtained by the experiment is, the stronger is the exponential relationship between the permeability and the effective stress, and the stronger is the stress sensitivity of the shale. Shen et al 9 found that the permeability sensitivity of shale fractures under stress was very strong, and the exponential relationship better described the pressure dependency of the permeability for the tested shale samples. For high‐pressure deep shale gas reservoirs, which ware usually highly stress‐sensitive, the impact of strong stress sensitivity should be fully considered 10 .…”
Section: Introductionmentioning
confidence: 97%